TEACHERS STRATEGY IN TEACHING NARRATIVE TEXT AT SENIOR HIGH SCHOOL - Ade Elvina Harianja and Muhammad Natsir (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study is a qualitative descriptive. This research was conducted by direct observation of English teachers. This research was conducted by direct observation of the teacher in the classroom and by interviewing. Researchers studied four English teachers and gave the same four questions to each teacher. Indicators of success include three English teachers use cooperative strategy. The results of this study showed that three out of four English teachers who are in SMA Negeri 1 OnanRunggu using cooperative strategies in the teaching of narrative text. That means that 75% of 100% choose to use a cooperative strategy. Thus, it is suggested that the english teachers apply strategy cooperative when teaching narrative text.